Beyond Old Pipes and Ailing Budgets: Systems Thinking on Twenty-First Century Water Infrastructure in Chicago - Erban, Laura E.; Walker, Henry A. (Frontiers in Built Environment, 2019)
Cities are increasingly burdened by aging water infrastructure. Deferred maintenance and upgrades are compounded by emerging concerns over contaminants, extreme weather events, demographic shifts, equity and affordability of water services. These and other evolving 21st century conditions prompt changes to urban water infrastructure and related systems that have wide ranging outcomes. This work demonstrates two complementary techniques for analyzing these complex systems, through the example case of Chicago. Chicago has some of the oldest urban water infrastructure in the US and supplies drinking water to more than 5 million people. Recent efforts to improve the physical and financial components of Chicago’s water system have run into a gamut of social and environmental issues. Here, the socio-environmental systems (SES) context for Chicago’s water infrastructure is structured using a rigorous systems thinking method and visual grammar to map the SES in terms of distinctions, systems, relationships and perspectives (DSRP). DSRP maps structure information about how water flows through city and how money flows through the public utilities responsible for drinking water delivery, wastewater treatment and stormwater management. Flows are evaluated, using open data and methods, over a 23-year period (1995-2017). Overall declines in water use and wastewater production are accompanied by an increase in the costs of water services, costs that support not only water infrastructure operations, maintenance and capital improvements, but also other municipal functions. Trends in the integrated data are interpreted through iterative refinement of DSRP maps to include additional components and to consider the SES from different points of view. Findings suggest that systems thinking is important for designing urban water system upgrades that are responsive to diverse socio-environmental concerns. As changes are made, transparent, reproducible methods for tracking outcomes can support analysis of differential impacts on users. The methods applied here at the city scale may be used to better understand localized, complex issues surrounding water infrastructure upgrades in Chicago and other cities.